Creature Comfort: Foundations for Christian Hospitality Toward Non-Human Animals - Matevia, Marilyn L. (Journal of the Society of Christian Ethics, 2020)
Can human co-existence with wild animals can be mediated by an ethic of hospitality? Some Christian environmental and animal ethicists have outlined ways Christians can model a more expansive, imaginative, and informed hospitality toward non-human animals. This paper will explore philosophical and theological underpinnings for such a practice, to ask whether it can have any prescriptive “teeth” when the interests of humans and non-human, non-domestic animals collide in ways that humans perceive as costly. The paper will argue that a commitment to interspecies hospitality can indeed function as a biocentric and biblical form of justice that adapts and extends community to our fellow creatures.